INNOVATIVE METHODS IN DEVELOPING INFORMATION SECURITY SKILLS IN STUDENTS - Mirzayev Tolibjon (Modern American Journals, 2025)
The article analyzes the role and importance of innovative technologies in the formation and development of the necessary competencies in Information Security students. Training qualified specialists who can fight Information threats in today's digital society is one of the urgent tasks facing the educational system. In this regard, the article offers improved approaches based on the use of modern information and communication technologies, multimedia tools and digital interactive techniques. Through this methodology, students not only acquire theoretical knowledge, but also effectively master practical skills.
Keywords: Innovative technologies, information security, competence, educational process, digital literacy, computer engineering, pedagogical methodology, ICT tools, student activities.